Living on the moon - Baker, David, 1944-; Kissock, Heather (New York : Weigl Publishers, 2010)
Offers students an overview of NASA's plans to build a research station on the Moon, describing the innovative techniques, materials, and equipment that will be used to create the research center.
Earth's sister world -- Moon facts -- Apollo exploration -- What scientists learned -- Building blocks -- Stepping stone -- Designing for the moon -- The new mission -- Visiting the space station -- Heavy lift -- The lunar bug -- To the moon/to stay -- Building a base -- A bridge to the moon -- Habitats -- Getting around -- Science on the moon -- What we have learned.
Includes bibliographical references (p. 30) and index.
6.5
3-6
Keywords: Moon -- Juvenile literature; Moon -- Exploration -- Juvenile literature; Moon; Moon -- Exploration; Moon; Moon -- Exploration